ANALYZING ISLAMIC ARCHITECTURE VISUAL QUALITY IN BUSHEHR CITY; CASE STUDY: RELIGIOUS SPACE KAZERUNI BARHAH (HOSSEINIYE) - Alalhesabi, Mehran; Hosseini, Seyyed Bagher; Nassabi, Fatemeh; Sedhpour, Bahram Saleh (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2012)
Islamic architecture can be studied from different aspects. This paper introduces a religious place in Bushehr city of Iran, a Bahrah or Hosseiniye that is used in especial religious ceremony and was built a century ago and after recent renovations is still in use and applicable. The research tries to quantify and analyze its visual quality as an important quality in the built environment with a tool called isovist in Syntax 2D software. In this study isovist indexes of six different spaces have been evaluated in this. The research shows interesting findings of spatial form and location and its visibility; for example it shows that spaces with circulation role have more visibility also spaces of the higher floor show higher visibility than the ground floor. Keywords: Visibility analysis, Syntax2D, religious space, isovist, Barhah